ROLE OF IRON DEFICIENCY ANEMIA IN EXACERBATION OF HEART FAILURE IN PATIENTS WITH DILATED CARDIOMYOPATHY - REHMAN , AU; HASSAN , K; MEHMOOD , S; ASHRAF , A (Biological and Clinical Sciences Research Journal, 2024)
Patients with heart failure (HF) frequently suffer from anemia. However, there are significant differences in the prevalence, prognostic factor, and clinical impact of anemia in individuals with heart failure. This study shows clinical characteristics and outcomes of severe heart failure patients with anemia who were admitted to Khyber Teaching Hospital Peshawar (KTH) in order to assess the incidence of worsening heart failure in anemic patients. Method: A cross-sectional study was carried out, and we evaluated the medical records of patients with heart failure who were admitted to Khyber Teaching Hospital between August 2023 to January 2024 All HF patients’ independent predictors of mortality were examined using multivariate Cox regression. Statistical significance was defined as a P value of less than 0.05.Result: The study included one hundred patients. The study found that 70% of individuals had anemia, and 60% of the participants were female. The levels of salt, creatinine, and hemoglobin in anemic patients differed significantly. Based on hemoglobin level, a more significant difference was seen among research participants (Log rank test, P = 0.001). Additionally, multivariate Cox regression revealed that total mortality was independently predicted by advanced age, lower salt levels, and higher creatinine levels. Conclusion: Heart Failure patients with anemia tend to be older age, had lower hemoglobin and sodium level and higher creatinine value. Moreover, there was a significant difference in the prognosis of anemic Patients, tend to have a worse survival status. Even though, anemia is a significant risk marker, exacerbating heart failure, it is not an independent predictor of mortality in the current study.